A Critical Review of the Indonesian Translation of "Be a Coronavirus Fighter" - et. al., Alvii T.B. Siregar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper aims to offer criticism on an Indonesian translation of "Be a Coronavirus Fighter." The book is one of the children's literature collections that discusses how children should view the pandemic and protect themselves from the virus. The study employed a systematic evaluation based on Berman's methods by comparing the English and Indonesian text versions. The Indonesian translation was done by Emil Salim, a well-known figure in the translation industry. At a macro level, high adherence was found in text function consistencies, catering to educating young readers about the virus and its effects. At a micro level, however, some expressions were translated in adult-level and less-contemporary language. A conclusion can be drawn that it should use a more contemporary children's language level to represent the original text better.